Pine wood shavings contribute non-denitrifying nitrate reducers and microeukaryotes to permeable barrier microcosms - Berardino-Lang, Gail, author; DuTeau, Nancy, advisor; Ethridge, Frank G., committee member; Gentry-Weeks, Caludia, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2005)
Wood products are used in permeable barriers as a reductant to enhance microbial denitrification to decrease the amount of nitrate from agricultural runoff which enters into tributaries in an effort to control the hypoxia that threatens fishing and recreational industries. Data with regards to the identities of the microbial populations in permeable barriers, especially denitrifiers and other nitrate reducers are required to design and manage permeable barriers for denitrification. Jar, syringe and flow-through column permeable barrier microcosms were analyzed. Diversity was assessed through EL-FAME ordination and fatty acid profiles by treatment while nitrate reduction activity was determined in isolates cultured anaerobically on high protein media with potassium nitrate. Isolates were subsequently tested for denitrification ability in durham tubes containing nitrate broth. Addition of wood to soil in a permeable barrier affects the number of denitrifiers introduced as well as competing nitrate reducers and microeukaryotes. Abundant fatty acids in wood are produced by microeukaryotes while the abundant fatty acids in soil, exclusive of water samples, are produced by eubacteria. Microeukaryotes contribute to temporary fixation of nitrate in biomass as well as the release of ammonium through grazing of bacteria. There are significantly more culturable nitrate reducers in permeable barrier microcosms than in soil controls. Wood controls have significantly more culturable nitrate reducers than soil; therefore, addition of wood increases nitrate reduction through the introduction of microbes as well as from the addition of carbon. Less than 1% of nitrate reducer isolates from wood denitrified which suggests that the majority of nitrate reducers in wood are non-denitrifying or that denitrification ability is inhibited by the wood. The denitrifiers most commonly isolated from permeable barrier microcosms are fluorescent pseudomonads and Azospirillum species which are potential candidates for denitrifier supplementation due to their ability to compete with non-denitrifiers, elude grazing, survive during periods of low nitrate input and scavenge micronutrients. Water samples from permeable barrier microcosms have less variance than solid samples, equal numbers of nitrate reducers and higher odds for isolation of denitrifiers which indicates that samples from wells and effluent from permeable barriers are important for analysis of denitrifiers in permeable barriers.
Keywords: microbiology; environmental engineering